(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2018)
The essay examines post-Maoist cinema by looking at two interrelated issues: the portrayal of sexuality and cinephilia during the Maoist period. Sexual urges are inextricable from post-Maoist cinema; in particular, the connection between eros and revolution serves to criticize Maoism from within. Another common trait is the long shadow cast by lms made in the Maoist period. Whether by explicit reference to movie-going in the diegesis or through allusions understood by those familiar with Maoist oldies, post-Maoist cinema tends to be highly cinephilic. The onscreen reemergence of cinephilia – often in conjunction with the eruption of youthful libido – is no low-stakes game; rather, it enables a critical view of Maoism. This essay focuses on The Dreamers (The Dreamers - I sognatori, Bernardo Bertolucci, 2003) through a diachronic and synchronic lens, placing the lm side by side with other movies – the historical precedent La Chinoise (Jean-Luc Godard, 1967) and the roughly contemporary Chinese lm In the Heat of the Sun (Yangguang canlan de rizi, Jiang Wen, 1994).